KAJI ULANG STATUS GIZI ANAK 0-59 BULAN (BERAT BADAN MENURUT UMUR) MENGGUNAKAN DATA NASIONAL: SUSENAS 1989-2005 PERBANDINGAN STANDAR NCHS/WHO DAN RUJUKAN WHO 2005 - ., Atmarita (PERSATUAN AHLI GIZI INDONESIA, 2008)
REASSESSMENT OF NUTRITIONAL STATUS (WEIGHT OF AGE) FOR CHILDREN 0-59 MONTHS USING NATIONAL DATA SUSENAS 1989-2005 COMPARISON OF WHO STANDARDS AND NCHS REFERENCEIn April 2006, the World Health Organization has launched new standards for assessmentgrowth and development of children 0 to 5 years of age. This new standards should beadopted in all countries. Nationally, Indonesia has been collecting anthropometric data forchildren under five since 1989 up to 2005 through periodic socio-economic national survey(SUSENAS). The nutritional status based on weight for age using NCHS reference has beenassessed to monitor the change of underweight prevalence, especially at provincial andnational level. The new standards need to be applied for reassessing the underweightprevalence as part of adoption process. The primary source of data is the 1989-2005Susenas’ Surveys, both the household data, and the individual data, along with thenutrition module. Weight for Age data on nutritional status is described in Z scores fromboth the NCHS international reference and new WHO standards. Descriptive analyses werecarried out reviewing the trend of underweight prevalence from 1989 to 2005, mean weightof children under five both for sexes, the prevalence of underweight across the provincesand by age groups as well both sexes, mean z-scores by age and quintiles, and distributionby quintiles. The results from reassessment showed that the prevalence of moderateunderweight generally higher using new WHO standard compared to NCHS/WHOreferenceduring the first half infancy 0-5 months and lower for the age above 6 months.However, the prevalence of severe underweight generally higher based on WHO standardcompared to NCHS/WHO reference. Differences in prevalence between WHO standard andNCHS reference vary by location (urban, rural), economic status depend, age group, sex, orother population characteristics.Keywords: comparison, reassessment, underweight prevalence